2021
DOI: 10.1097/prs.0000000000008388
|View full text |Cite
|
Sign up to set email alerts
|

Long Pedicled Superficial Circumflex Iliac Artery Flap Based on a Medial Superficial Branch

Abstract: To cover a 6 × 3-cm defect caused by diabetic ulceration, a superficial circumflex iliac artery perforator free flap with a 7-cm pedicle was elevated. Microanastomosis was performed to the first dorsal metatarsal artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Kwon et al [ 21 ] made some modifications in the dissection of the SCIA flap by marking the medial border of the flap away from the pubic tubercle and dissecting the flap superficial to superficial fascia, thereby obtaining a good pedicle length of 6 to 8 cm. Still, his modification requires preoperative angiogram which is not cost-effective in our setup, and we got the desired pedicle length by traditional SCIA flap, and none of our anastomosis required intervening vein graft.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al [ 21 ] made some modifications in the dissection of the SCIA flap by marking the medial border of the flap away from the pubic tubercle and dissecting the flap superficial to superficial fascia, thereby obtaining a good pedicle length of 6 to 8 cm. Still, his modification requires preoperative angiogram which is not cost-effective in our setup, and we got the desired pedicle length by traditional SCIA flap, and none of our anastomosis required intervening vein graft.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown the stability and reliability of the adipofascial flaps for facial reconstruction 6 . Because SCIA and SIEA are mainly located in the fatty tissue, flap elevation would primarily proceed between the superficial fascia and subdermal layer, avoiding intramuscular dissection and lymphatic impairment 2,13,24 . This greatly differs with a conventional muscular cutaneous flap such as ALT.…”
Section: Discussionmentioning
confidence: 99%
“…17 21 Moreover, a relatively long pedicle can also be obtained by making the flap design more lateral and distal. 22…”
Section: Discussionmentioning
confidence: 99%
“…17,21 Moreover, a relatively long pedicle can also be obtained by making the flap design more lateral and distal. 22 The superficial circumflex iliac artery (SCIP) flap has been recently popular in the last decade. The main advantages of this flap are the availability of thin flaps and the minimal donor site morbidity with concealed donor sites.…”
Section: Accepted Manuscriptmentioning
confidence: 99%